STRATEGI KESANTUNAN BERBAHASA INDONESIA DALAM PEMINIMALAN BEBAN DAN PAKSAAN DI KALANGAN WARGA KAMPUS UNIVERSITAS JAMBI - Akhyaruddin Akhyar (Program Studi Pendidikan Bahasa dan Sastra Fakultas Keguruan dan Ilmu Pendidikan Universitas Jambi, 2017)
One ofthe ways used by speakers of a language to build social relationship particularly in smoothing demand or cuercion is to use politensess form how to speak. Used a polite form were influenced by five parameters, namaly: older speakers or higher position an its relation to familiar speakers (+K+S); spekers are older or of higher social status and relationship with the speakers not familier (+K-S); hearer and speaker the same age or the same position and both intimate relationship (=K+S); speakers youngeror lower position, but the relationship with the speakers familiar (-K+S); and hearer or talk to younger or lower position and relationship with the speakers not familiar (-K-S). University Jambi among campus resident, linguistic politeness form are used to minimize the hearer coercion by parameters is (1) the use of conditional requets, (2) the use of the formula sugegestion, (3) disclosure of hope, (4) the use of a questionnaire, (5) the use of the greeting kinship.